Evaluation of I‐Gel™ size 2 airway in different degrees of neck flexion in anesthetized children – a prospective, self‐controlled trial. Issue 12 (25th October 2016) - Jain, Divya; Ghai, Babita; Gandhi, Komal; Banerjee, Gargi; Bala, Indu; Samujh, Ram
Summary: Background: A previous study by our group demonstrated an increase in oropharyngeal leak pressures and a deterioration of ventilation in maximum neck flexion with the I‐Gel ™ . To ascertain the optimal degree of neck flexion which increases OPLP without compromising ventilation we conducted a prospective self‐controlled trial with the I‐Gel ™ in different degrees of neck flexion in anesthetized paralyzed children. Methodology: The I‐gel ™ was inserted in 60 children undergoing inhalation induction with muscle paralysis for routine general anesthesia. Recordings of peak inspiratory pressures (PIP) at flexion of 15°, 30°, and 45° were taken as the primary outcome. Expired tidal volume, ventilation scoring, fiberoptic gradings, and OPLP in different degrees of flexion were recorded as secondary outcomes. Results: There was a significant increase in mean PIP in cm H2 O at flexion 30° [13.3 (95% CI 12.8–13.8) cm H2 O, P < 0.001] and 45° flexion (16.5 [15.9–17.1] cm H2 O, P < 0.001) compared to neutral. A decrease in the expired tidal volume was seen at flexion of 30° (7.6 [7.3–7.8] cm H2 O, P = 0.00) and 45° (7.6 [7.3–7.8] cm H2 O, P = 0.00). There was deterioration of ventilation score, mean [range] at 30° flexion 2[0–3], and 45° flexion 1[0–3] compared to the neutral 3[2–3]. There was a significant increase in OPLP with an increase in degree of flexion. Conclusion: We conclude that 15° neck flexion can safely be applied without compromising ventilation with the I‐Gel ™ in anesthetized paralyzed children. However, Flexion of 30° or more warrants caution or the use of alternative devices like an endotracheal tube due to increase in PIP and worsening of ventilation score. Abstract :